2019
DOI: 10.3390/cells8111440
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSCs-Derived Endothelial Cells with Mutation in HNF1A as a Model of Maturity-Onset Diabetes of the Young

Abstract: Patients with HNF1A-maturity-onset diabetes of the young (MODY) often develop endothelial dysfunction and related microvascular complications, like retinopathy. As the clinical phenotype of HNF1A-MODY diabetes varies considerably, we used human induced pluripotent stem cells (hiPSCs) from two healthy individuals (control) to generate isogenic lines with mutation in HNF1A gene. Subsequently, control hiPSCs and their respective HNF1A clones were differentiated toward endothelial cells (hiPSC-ECs) and different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…These mutations may cause abnormal transcription and translation, eventually leading to changes in phenotype and function. 24 HNF1A was reported to interact with other genes and pathways in cancer, 25,26 which is consistent with our results. These phenomena may explain the distinct prognostic value of HNF1A in different types of cancers.…”
Section: Discussionsupporting
confidence: 92%
“…These mutations may cause abnormal transcription and translation, eventually leading to changes in phenotype and function. 24 HNF1A was reported to interact with other genes and pathways in cancer, 25,26 which is consistent with our results. These phenomena may explain the distinct prognostic value of HNF1A in different types of cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, these models provide human-relevant information on disease mechanisms or drug responses, as compared to various animal models. As discussed above, hiPSCs demonstrate the capacity to efficiently differentiate into various cell types including ECs [92]. Importantly, many studies have already confirmed that patient-specific hiPSC-derived ECs recapitulate the specific pathological phenotype observed in a particular disease, either with a known genetic background or complex etiology and systemic course [93,94].…”
Section: Hipsc-ecs In Disease Modelingmentioning
confidence: 89%
“…GATA4 was identified as a potential target while surveying the genome of such patients, and its mutation was associated with impaired endothelial-to-mesenchymal transition, a process important for normal aortic valve formation [101]. Similarly, in our studies using hiPSCs isogenic lines generated through the introduction of mutation in hepatocyte nuclear factor 1A (HNF1A), we aimed to model the endothelial state of patients with maturity onset diabetes of the young (HNF1A-MODY) [92]. In our hands, hiPSC-ECs expressed typical endothelial markers, exerted angiogenic functionality, properly responded to inflammatory cytokines as well as shear stress (Figure 5).…”
Section: Monogenic Diseasesmentioning
confidence: 99%
“…hiPSC.1 expressed pluripotency markers: NANOG, OCT4, SSEA4, TRA-1-60, TRA-1-81 ( Supplementary Figure S2 A), and spontaneously differentiated in vitro via EBs into cells originating from three germ layers (mesoderm, endoderm, and ectoderm— Supplementary Figure S2B ). Karyotype of all hiPSCs was examined ( Supplementary Figure S3 ) Pluripotent properties of hiPSC.2 and hiPSC.3 were characterized in our previous studies [ 17 , 18 ] (respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Verified hiPSCs were cultured as described previously [ 18 ]. hiPSCs were differentiated to cardiomyocytes utilising the GiWi protocol, described by Lian et al [ 8 ].…”
Section: Methodsmentioning
confidence: 99%